2012
DOI: 10.1109/tsg.2012.2198499
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Roles of Unit and Non-unit Protection Methods Within DC Microgrids

Abstract: The characteristic behavior of physically compact, multiterminal dc networks under electrical fault conditions can produce demanding protection requirements. This represents a significant barrier to more widespread adoption of dc power distribution for microgrid applications. Protection schemes have been proposed within literature for such networks based around the use of non-unit protection methods. This paper shows however that there are severe limitations to the effectiveness of such schemes when employed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(79 citation statements)
references
References 17 publications
0
79
0
Order By: Relevance
“…Another publication [42] argues for the use of unit protection in more complex DC microgrids to achieve better fault discrimination. This necessitates the use of additional communication and relay technology.…”
Section: Ieds Communication and Differential Protectionmentioning
confidence: 99%
“…Another publication [42] argues for the use of unit protection in more complex DC microgrids to achieve better fault discrimination. This necessitates the use of additional communication and relay technology.…”
Section: Ieds Communication and Differential Protectionmentioning
confidence: 99%
“…Reference [8] had investigated a range of protection solutions and reported that the differential current scheme is suitable for the DC system. Differential protection has highest selectivity, and only operates in case of internal fault.…”
Section: Introductionmentioning
confidence: 99%
“…Due to fast fault protection and control requirements, timely fault detection, location, and coordination methods, are challenging for DC protection [9][18] [29]- [43]. An overview of different protection methods for DC protection can be found in [9] [29].…”
Section: Introductionmentioning
confidence: 99%
“…An overview of different protection methods for DC protection can be found in [9] [29]. Traditional overcurrent and di/dt protection [30]- [33] can still be applied in some distribution networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation